Structural Optimization of Tri-Cone Cyclone Based on the Response Surface Method - Qian Weifeng; Zhou Sizhu; Zhuang Hao; Huang Tiancheng; Yao Zhoukun (Shiyou jixie)
There are scarce reports on the separation performance of discontinuous multi-cone cyclones. This paper presents a combined tricone cyclone structure. First， a numerical simulation was conducted for single factor analysis on the main structure， so as to identify the influence of each factor on the separation efficiency. Second， based on the Plackett⁃Burmann test， the influence weight of each factor was determined， and three important factors were selected. Third， combined with the steepest climbing test and response surface design， the three factors were optimized， and the fitting equations between different factors and overall separation efficiency were obtained. Finally， the interaction between pairwise factors was analyzed to explore their influence on the overall separation efficiency. The results show that the optimal parameter combination is as follows： main diameter of 76.354 mm， upper cone length of 80 mm， and underflow opening diameter of 18.495 mm， corresponding to a gas separation efficiency of 96.697%， a solid separation efficiency of 86. 983%， and an overall separation efficiency of 94.258%. The conclusions provide a theoretical reference for the research of separation performance of multi-cone cyclones.